Pengendalian Kualitas Produk Mainan Melalui Pendekatan Metode Six Sigma pada PT Langgeng Buana Jaya - Dwi Pramana Putra; Abdurrahman Faris Indriya Himawan (Universitas Muhammadiyah Gresik, 2022)
In general, the company always pays attention to the quality of its products, which with good quality will increase consumer confidence in PT Langgeng Buana Jaya has implemented a production quality control system. However, in reality there are still products that are of poor quality, so it is necessary to analyze the quality control efforts implemented by the company and find out what causes the problem and look for improvement solutions using the Six Sigma method. The purpose of this study is to analyze and implement quality control of toy products at PT Langgeng Buana Jaya using the Six sigma approach. This research is a type of qualitative research and test the validity of this research data using source triangulation. The causes of product defects at PT Langgeng Buana Jaya based on the fishbone diagram are product defects due to stitches, scratches and color effects. This research contributes to minimize product defects by using the six-sigma method. Better prepare themselves in the process of collecting and collecting data and for further researchers it is hoped that they can conduct continuous research until the sigma number is high and the results can be even better. In general, the company always pays attention to the quality of its products, which with good quality will increase consumer confidence in PT Langgeng Buana Jaya has implemented a production quality control system. However, in reality there are still products that are of poor quality, so it is necessary to analyze the quality control efforts implemented by the company and find out what causes the problem and look for improvement solutions using the Six Sigma method. The purpose of this study is to analyze and implement quality control of toy products at PT Langgeng Buana Jaya using the Six sigma approach. This research is a type of qualitative research and test the validity of this research data using source triangulation. The causes of product defects at PT Langgeng Buana Jaya based on the fishbone diagram are product defects due to stitches, scratches and color effects. This research contributes to minimize product defects by using the six-sigma method. Better prepare themselves in the process of collecting and collecting data and for further researchers it is hoped that they can conduct continuous research until the sigma number is high and the results can be even better.